2022
DOI: 10.3889/oamjms.2022.8974
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Level and Risk of Anemia in Soil-Transmitted Helminths Infections among Children: A Systematic Review and Meta-analysis

Abstract: Introduction. Soil Transmitted Helminthiasis (STH) is a Neglected Tropical Disease with almost 25% world population infected. Children were vulnerable to infection with morbidities affecting growth. STH infection alters children nutritional status which potentially causing anemia. Meta-analysis relating STH infections to hemoglobin (Hb) level and risk of anemia in children is limited. Aim. To compare hemoglobin levels and risk of anemia in children infected and uninfected with STH. Methods. Meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…A meta-analytical study confirmed the direction of this effect by reporting a high OR 4.49, 95% CI 1.58 to 12.75, p < 0.05 among children with multiple STH infections [50]. The study delineated the effect of single STH parasites on child anemia and reported the greatest risk of anemia among hookworm-infected children with OR 3.3, 95% CI 1.98 to 5.49, p < 0.05, while A. lumbricoides had OR 1.57, 95% CI 1.2 to 2.07, p < 0.05 and T. trichiura with OR 1.66, 95% CI 1.13 to 2.43, p < 0.05 [50]. These results confirm the hypothesis that among children who are infected with STH, the mean hemoglobin levels are significantly lower in individuals with polyparasitism (referring to individuals harboring more than 1 helminth species in their body) [51].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 88%
See 2 more Smart Citations
“…A meta-analytical study confirmed the direction of this effect by reporting a high OR 4.49, 95% CI 1.58 to 12.75, p < 0.05 among children with multiple STH infections [50]. The study delineated the effect of single STH parasites on child anemia and reported the greatest risk of anemia among hookworm-infected children with OR 3.3, 95% CI 1.98 to 5.49, p < 0.05, while A. lumbricoides had OR 1.57, 95% CI 1.2 to 2.07, p < 0.05 and T. trichiura with OR 1.66, 95% CI 1.13 to 2.43, p < 0.05 [50]. These results confirm the hypothesis that among children who are infected with STH, the mean hemoglobin levels are significantly lower in individuals with polyparasitism (referring to individuals harboring more than 1 helminth species in their body) [51].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 88%
“…For example, in Ethiopia, children infected with intestinal helminths were highly likely to have anemia (aOR 8.87, 95% CI 2.28 to 34.58) [ 49 ]. A meta-analytical study confirmed the direction of this effect by reporting a high OR 4.49, 95% CI 1.58 to 12.75, p < 0.05 among children with multiple STH infections [ 50 ]. The study delineated the effect of single STH parasites on child anemia and reported the greatest risk of anemia among hookworm-infected children with OR 3.3, 95% CI 1.98 to 5.49, p < 0.05, while A .…”
Section: 0 Co-infection With Other Diseases: Burden Etiology and Impl...mentioning
confidence: 99%
See 1 more Smart Citation